2010
DOI: 10.1007/s10554-010-9770-5
|View full text |Cite
|
Sign up to set email alerts
|

99 mTc-MIBI washout as a complementary factor in the evaluation of idiopathic dilated cardiomyopathy (IDCM) using myocardial perfusion imaging

Abstract: Rapid technetium-99 m methoxyisobutylisonitrile (99 mTc-MIBI) washout has been shown to occur in impaired myocardia. This study is based on the hypothesis that scintigraphy can be applied to calculate the myocardial 99 mTc-MIBI washout rate (WR) to diagnose and evaluate heart failure severity and other left ventricular functional parameters specifically in idiopathic dilated cardiomyopathy (IDCM) patients. Patients with IDCMP (n = 17; 52.65 ± 11.47 years) and normal subjects (n = 6; 49.67 ± 10.15 years) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Additionally, it appears to have a role in the diagnosis and staging of tumors, and in the noninvasive assessment of ischemia in patients with peripheral vascular diseases. 27 Results from the present study indicate that the lung uptake of 99mTc-MIBI was well-correlated with markedly abnormal in patients with ILD who had clinical and/or radiologic evidence of pulmonary involvement.…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, it appears to have a role in the diagnosis and staging of tumors, and in the noninvasive assessment of ischemia in patients with peripheral vascular diseases. 27 Results from the present study indicate that the lung uptake of 99mTc-MIBI was well-correlated with markedly abnormal in patients with ILD who had clinical and/or radiologic evidence of pulmonary involvement.…”
Section: Discussionsupporting
confidence: 50%
“…The heart-to-mediastinal ratio was calculated from planar images recorded at 40 min and at 4 h. The investigators found increased MIBI loss from the myocardium in patients with elevated left ventricular end-diastolic pressure and prolonged half-time of relaxation. In 17 patients with dilated cardiomyopathy (mean LVEF: 29%), Shiroodi et al (15) measured MIBI washout and compared the results to those from 6 normal subjects (mean LVEF: 66%). The investigators acquired images at 30 min and 3.5 h after injection.…”
Section: See Page 2007mentioning
confidence: 99%
“…Hayashi et al (16) used a slightly different protocol than did Shiroodi et al (15), recording MIBI images at 1 and 4 h after injection. Myocardial retention of MIBI was measured on planar images as: (initial net myocardial counts* -delayed net myocardial counts † )/initial net myocardial counts.…”
Section: See Page 2007mentioning
confidence: 99%
“…The heart-to-mediastinal ratio (HMR) was calculated from planar images recorded at 40 min and at 4 h. The investigators found increased MIBI loss from the myocardium in patients with elevated left ventricular end-diastolic pressure and prolonged half time of relaxation. In 17 patients with dilated cardiomyopathy (LVEF 29 %), Shiroodi and colleagues [26] measured MIBI washout and compared the results to six normal subjects (LVEF 66 %). Myocardial clearance was measured as the change in HMR at 30 min and 3.5 h after injection.…”
Section: Mitochondriamentioning
confidence: 99%